إشكالية الشرعية وعلاقة الدولة بالمجتمع: دراسة في النماذج والتطبيقات - سعداوي, نبيل (جامعة الوادي University of Eloued, 2019)
الملخص: تحاول هذه الورقة البحثية تسليط الضوء على إشكالية الشرعية وتأثيرها على علاقة الدولة بالمجتمع، من خلال التعرض إلى أبرز النماذج والتطبيقات العالمية، وذلك بالتطرق إلى كل من نموذج الشرعية الديمقراطية الرأسمالية، الذي عرف في كل من الولايات المتحدة الأمريكية وأوروبا الغربية ثم شهد رواجا في كل دول العالم نتيجة انتشار القيم الديمقراطية، وهو يقوم على مبدأ الشرعية الشعبية، أما النموذج الاشتراكي للشرعية فقد عرف في كل من الاتحاد السوفياتي سابقا وأوروبا الشرقية والصين، وقد عرف هذا النموذج تراجعه نتيجة اختلال العلاقة بين الدولة والمجتمع وازدياد حدة الأزمات الاقتصادية والسياسية والاجتماعية، أما النموذج الإسلامي للشرعية فيقوم على أن مصدر الشرعية هو الله مع الاعتماد على القرآن والسنة واجتهادات العلماء في تسيير شؤون الأمة وضرورة طاعة الحاكم، وقد شهدت العلاقة بين الدولة والمجتمع في العهد الأول متانة وتلاحما، إلا أن الانحراف الذي مس نموذج الشرعية الإسلامية وتأسيس نظم ملكية وكثرة الصراعات على السلطة أدى إلى سقوط عدد من الأنظمة السياسية نتيجة هذه العوامل التي أخلت بالعلاقة بين الدولة بالمجتمع، ومن هذه التجارب نجد الدولة الأموية والعباسية والعثمانية. الكلمات المفتاحية: الشرعية، الشرعية الديمقراطية، الشرعية الاشتراكية، الشرعية الإسلامية، علاقة الدولة بالمجتمع. Abstract: This research paper sheds light on the problem of legitimacy and its influence on the power and the society relations through addressing the prominent models and the international applications including: the Capitalist Democratic Legitimacy, the Communist Legitimacy, and the Islamic Legitimacy. Concerning the Capitalist Democratic Legitimacy model, it was known in USA and the Western Europe. Then, it witnessed a worldwide spread because of the proliferation of the democratic values. It’s based on the Peoples Legitimacy Principal. Regarding the Communist Legitimacy model, it was known in the Soviet Union [previously], the Eastern Europe, and China. As a result of a misfire in the power and the society relation and the political, economic, and social crisis increased tension, it moved back. As for the Islamic Legitimacy model, it’s based on God, with the reliance on Quran and Sunnah, in addition to scientists’ diligence in managing the nations’ affairs and the necessity of obeying the ruler. The power and society relation had witnessed a durability and cohesion, in the first era, but the Islamic Legitimacy deviation, the rising of monarchs, and many struggles for power led to the collapse of many political systems such as: the Umayyad, Abbasid states, and the Ottoman Empire, because of these factors that corrupted the power and the society relations. Key words: the Legitimacy, the Democratic Legitimacy, the Communist Legitimacy, the Islamic Legitimacy, and the power and society relations. Keywords: legitimacy, democratic legitimacy, socialist legitimacy, Islamic legitimacy, the state's relationship with society.
Keywords: الشرعية - الشرعية الديمقراطية - الشرعية الإسلامية - علاقة الدو لة بالمجتمع